Using edge‐of‐field monitoring to characterize water quality: A farmer cooperative case study in northern Missouri. Issue 3 (6th August 2021) - Udawatta, Ranjith P.; Jose, Shibu; Hefner, Steven; Brinkman, Karen
Abstract: Edge‐of‐fieldwater quality monitoring was conducted in cooperation with private landowners through the Mississippi River Basin Healthy Watershed Initiative, a landscape conservation program first offered through the USDA‐NRCS in 2010. The study objective was to quantify effectiveness of individual conservation practice or practice combinations on water quality on corn ( Zea mays L.)‐soybean [ Glycine max (L.) Merr.] watersheds. Water samples from northern Missouri farms were collected and analyzed by runoff event for sediment (total suspended solids [TSS]), N, and P to evaluate the effects of crop production, residue types, and conservation land treatment on runoff. The presence of living vegetation in the winter, whether established as a cover crop or cash crop, significantly reduced the sediment loads ( p  < .0001) and nutrient loads ( p ≤ .0077). Additional benefits occurred on sites that produced higher residues, like corn or corn with winter wheat ( Triticum aestivum L.). Significantly low TSS losses occurred during soybean years with corn and winter wheat residues. Sites that implemented full land treatment, having conservation practices that serve to avoid, control, and trap a pollutant, were more effective than those with fewer treatments, especially with respect to P loading. The mean rank for orthophosphates was 45% lower from sites with avoid, control, and trap practices instead of control practices only. Data support the conclusion that conservation structural and management practices are effective and can mitigate some negative impacts generated by agriculture. Although an intricate endeavor, edge‐of‐field water quality monitoring can serve to complement other forms of environmental analysis and inform landowners about efficient farming practices. Core Ideas: The Mississippi River Basin Healthy Watershed Initiative was implement to improve water quality. Conservation practices improve water quality and reduce sediment and nutrient losses. Farmer cooperative research is more effective in promoting adoption of conservation practices.